Policies and interventions: Overview - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
The early work on intrahousehold allocation alerted researchers and policymakers to the possible policy failures that could arise from neglect of intrahousehold allocation issues (Haddad, Hoddinott, and Alderman 1997). Conversely, what are the policy gains from paying attention to these issues? The new research on intrahousehold issues provides evidence that policies and interventions can be made more effective when differential rights, resources, and responsibilities within the household are explicitly considered.